Design and Development of Some Pyrimidine Analogues as an Anthelmintic Agent (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Anthelmintic drugs are used to treat parasitic infections and acknowledge the challenge in developing effective anthelmintics due to the significant homology between parasites and their hosts. Despite the existence of various anthelmintic drugs in the market, the emergence of drug resistance necessitates the continuous development of new and more efficient drugs to combat parasitic infections. The development of anthelmintic drugs involves a multi-faceted process that aims to create effective treatments against parasitic infections. Pyrimidines have been investigated for their potential anthelmintic activity. Therefore, the present study involves the synthesis of derivatives based on pyrimidine. The series of 4-amino-2-hydroxy-6-substituted phenyl pyrimidine-5-carbonitrile was synthesized by treating substituted benzaldehyde with malononitrile and urea. The synthesized compounds were subsequently screened for their anthelmintic efficacy. The chemical structures were confirmed by infrared (IR) and proton nuclear magnetic resonance (1H-NMR) spectroscopy. The anthelmintic activity was performed on the adult Indian earthworm Pheretima posthuma. In-vitro anthelmintic studies revealed that, among all the screened compounds, compound 1f demonstrated significant or appreciable anthelmintic properties. Molecular docking was conducted on quinol-fumarate reductase to elucidate potential interactions between the newly synthesized pyrimidine derivatives and the specific cavity of the quinol-fumarate reductase enzyme. This analysis aimed to gain insights into the binding interactions and the possible mechanism of action of the synthesized compounds.